The cultivation of skill - Hofer, Christine D. (My University, 1902)
Introduction: All educational inquiries assume that man is capable of individual improvement, and therefore he is collectively progressive. He is slowly but surely civilized through the various experiences of life, and through experience there is a growth of knowledge. Mental discipline is the true object of a higher culture and for this the study of mathematics is especially beneficial. In olden times there was a great deal of superstition about the number seven. “It was supposed to be a key to the order of the universe. There were seven cardinal virtues, seven deadly sins, seven sacraments, seven days in the week, seven metals, seven planets, seven apertures to a man’s head.” Those believing this thought a person should study seven arts in seven years. In this day of specialities one art well learned is better than a great many partially learned.
Citation: Hofer, Christine D. The cultivation of skill. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Education; Mental Discipline; Learning; Skills; Theses; Manuscripts (documents)